Emotional intelligence and interpersonal communication skills accounting students - Garcia, Isabel Cristina Martin; Meurer, Alison Martins; Musial, Nayane Thais Krespi (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Analyze the relationship between emotional intelligence and interpersonal communication skills in accounting students. Methodology: A survey was conducted with academics from four higher education institutions in the southern region of Brazil, obtaining 202 valid responses. The relationships were analyzed using Structural Equation Modeling (SEM). Results: We found a positive relationship between the dimensions of Emotional Intelligence and Interpersonal Communication Skills, except for the Assessment of Own Emotions on Assertiveness, which showed a negative relationship. Furthermore, different dimensions did not show a significant relationship. Contributions of the Study: The results indicate that understanding one's own emotions (exercising self-control), recognizing the emotions of others (developing empathy), and using emotions (directing towards goals) have effects on the ability to manage interpersonal relationships in communication environments. Furthermore, identifying and understanding the nuances in verbal and non-verbal reactions facilitates communication, interpersonal relationships, and personal and professional growth. It is necessary to address this issue in undergraduate courses in Accounting Sciences, as the training and development practices of Emotional Intelligence and Interpersonal Communication Skills reflect on professional performance, convergence with the social skills required by the job market, and alignment with international standards for education. High-quality accounting and contribute to strengthening the profession.